Effects of lamotrigine on cortically-elicited phenomena in adult rats: differences between acute application and late consequences of early postnatal administration - Tsenov, Grygoryi; Redkozubova, Olga; Kubová, Hana; Mares, Pavel (Brain research, 2009)
Lamotrigine (LTG) is increasingly used in pediatric epileptology but there are no experimental data on delayed consequences of early life administration of LTG on epileptic phenomena. Therefore we used cortically induced epileptic phenomena to study these possible effects and compared the results with data on acute administration of LTG in adult rats. Naïve adult rats as well as animals with a history of LTG administration in early postnatal period (daily from postnatal day 7 to 11 in a dose of 10 and/or 20 mg/kg i.p.) were implanted with cortical stimulation and recording electrodes. Cortical interhemispheric responses and epileptic afterdischarges (ADs) were elicited by stimulation of sensorimotor area in both groups. Acute administration of LTG (10 and/or 20 mg/kg i.p.) did not affect cortical interhemispheric evoked responses but increased thresholds for elicitation of movements elicited by stimulation, spike-and-wave ADs and accompanying clonic seizures. On the contrary, duration of ADs was increased. Animals injected with LTG postnatally exhibited increased thresholds for transition of ADs into a limbic type (mixed ADs), decreased incidence of the limbic type and suppression of recurrent ADs. Evoked responses exhibited a steeper input-output curve in a group receiving the 20 mg/kg dose of LTG during early development. Our results demonstrated a specific anticonvulsant effect as a delayed consequence of early-life administration of LTG; it differed from effects of acute administration of LTG to adult rats.
Keywords: Animals; elektrická stimulace; novorozená zvířata; Electric Stimulation; Epilepsy; Rats, Wistar; Electrodes, Implanted; Lamotrigine; Anticonvulsants; lamotrigin; Animals, Newborn; antikonvulziva; Triazines; epilepsie; Male; evokované potenciály; Evoked Potentials; implantované elektrody; krysa rodu Rattus; triaziny; mozková kůra; Cerebral Cortex; zvířata; mužské pohlaví; elektroencefalografie; Rats; Electroencephalography; potkani Wistar